Black Lawyers and Civil Rights: The NAACP’s Legal Campaign Against Segregation - Leland Ware (Washington University Journal of Law and Policy, 2022)
While many remember the 1950s and ‘60s Civil Rights Movement as a grass-roots series of events consisting of mass marches, boycotts, and other protest activities, less is known about the carefully orchestrated series of lawsuits that occurred decades earlier. This Essay discusses the legal campaign against segregation by the NAACP working with national and local Black lawyers’ organizations. The Essay traces the development of the law from Plessy v. Ferguson’s establishment of the “separate-but-equal” doctrine to the execution of the “equalization” strategy that culminated with Brown v. Board of Education. Ware analyzes the impacts of these legal developments and the southern states’ “massive resistance” to school integration that remained post-Brown. The Essay concludes by discussing the lasting effects of discriminatory policies using the example of continuing segregation in neighborhoods and schools in many urban communities.
Keywords: Civil Rights; NAACP; Segregation; School Integration